PENGGUNAAN PREFIKS BAHASA INDONESIA DALAM PERCAKAPAN INFORMAL SISWA - Sunaryo Sunaryo (EDU-KATA, 2014)
The data of reseach were gathered from the students’ writing products from 6th graders of SDN Mojorejo, Kedungadem, Bojonegoro by using the instruments and agregation of data, data reduction, data display, and conclusion drawing/verification. The aim of study was to discribe the prefiks of Indonesian language from the students elementary’s informal conservation. The data of research show presence prefiks informal conservation from the 6th graders of SDN Mojorejo, Kedungadem, Bojonegoro. The teacher to expect teaching the meaning of grammatical and annexation the afiks with base word.